PENENTUAN PRIORITAS PENINGKATAN KUALITAS JASA DENGAN MENGGUNAKAN METODE IMPORTANCE-PERFORMANCE ANALYSIS (IPA) DAN INDEKS POTENTIAL GAIN CUSTOMER VALUE (PGCV) - Nur Hakim Arifianto; Sauptika Kancana; Adi Soeprapto (Jurnal Paradigma, 2019)
The purpose of the research is (1) analyzing the level of conformity betweenexpectations (importance) customer and performance (performance) of the company against the quality of services provided by Yamaha Motorcycle repair shop (2) Determine the priority Quality improvement based on the level of conformity and index of Potential Gain Customer Value (PGCV) to improve the quality of services provided by Yamaha Motorcycle repair shop. The population in this research is a customer Yamaha Motorcycle repair shop Demangan Yogyakarta for approximately arround 2 months April 2019 till June 2019.Determination of the number of samples will be determined by the level of Confidance 95% and margin of error is 10% then obtained the number of samples as many as 98 people. The sampling techniques used in this study were based on Non Probabiliy Sampling methods using the Accidental Sampling approach.The results showed that (1) the level of conformity between expectations (importance) of the customer and performance (performance) of the company against the quality of services provided by the Yamaha Motorcycle repair shop Demangan Yogyakarta has an average level of conformity Below 100% of which is 88.30%. 88.30% means the company lacks or does not fulfill what is considered important by the customer and the service has not beensatisfactory; (2) Priority of improvement of service quality (top priority in the Quadrant A IPA diagram with index PGCV) namely: 1) Workshop Yamaha new source Motor Demangan has a complete spare parts, 2) equipment used Yamaha Workshop new source Demangan complete, 3) Employees Yamaha Motorcycle repairshop Demangan tell the customers when the service is certainly motorbike will be delivered, 4) Employees Yamaha Motorcycle repair shop Demangan always ready in responding to customer demand, 5) Mechanics workshop Yamaha Motorcycle repair shop Demangan fast In servicing motorcycles, 6) Employees Yamaha Motorcycle repair shop Demangan always able to answer questions related to Yamaha motorcycles, 7) Employees Yamaha Motorcycle repair shop Demangan always prioritize the expectations of customers.